G-Protein Signaling Pathway (GP-SP) and Voriconazole-Resistance (VCZ-R) in Aspergillus species - Lulu Farhana; Jagdeesh Natesan; Suganthini Krishnan (Research Advances in Microbiology and Biotechnology Vol. 5, 2023)
The study aims to evaluate the possible role of G-protein signaling pathway genes in VCZ-R in Aspergillus species. Patients with compromised immune systems continue to have a large morbidity from invasive infections caused by Aspergillus species. Mortality is still high despite the availability of various azoles, including isavuconazole (ISZ), posaconazole (POS), voriconazole (VCZ), and itraconazole (ITZ). Several studies from cancer and transplant centres around the world have shown that azole resistance has emerged in clinical and environmental isolates of Aspergillus fumigatus and Aspergillus flavus. Using wild-type and particular mutant strains of Aspergillus species, CLSI based susceptibility and cyp51 gene-specific PCR studies were carried out to analyze the phenotypic changes and changes in the triazole-susceptibility pattern. It is plausible that several different signaling pathways function in Aspergillus spp. the G-protein signaling pathway has been shown to be a dominant regulator of conidiation in several closely related Aspergillus spp. Voriconazole inhibits conidiation in A. flavus, possibly through its effect on several genes involved in the GP-SP. Our findings imply that VCZ suppresses conidiation by concentrating on one of the crucial G-protein pathway genes, and that specific changes in these genes are probably responsible for the loss of conidiation and VCZ-R in A. flavus. Testing for cross resistance to additional triazoles, such as POS and ISZ, is also necessary. Our in vitro studies comparing the efficacy of azoles using conidia or hyphal masses as inoculums show that hyphae are more resistant to antifungal killing compared to conidia.